Verification of the Peleg and Normand Equation at Varied Loads and Moisture During Stress Relaxation of Wheat (Agricultural Engineering, 2019)
Wheat kernel is made up of structures of different apparent viscosities with varied ability to withstand stress and dissipate strain energy. Its complex mechanical behaviour determines technological susceptibility and is important for wheat quality assessment. The aim of the study was the examination of the Peleg and Normand model to characterize the overall stress relaxation behaviour of wheat kernel at varying loading conditions. The relaxation experiments were made with a help of a universal machine Zwick Z020 in compression at four distinct initial load levels, i.e., 20, 30, 40, and 50 N. The measurements were made for intact wheat kernels at seven levels of moisture content. Relaxation characteristics were approximated with the help of Peleg and Normand formula. An interactive influence of the load level and moisture on Peleg and Normand constants have been confirmed. The initial loading level had none or only slight effect on the model coefficients (Y(t), k1 and k2). The parameters of the Peleg and Normand model decreased with the increase of water content in kernels. For moist kernels, a higher amount of absorbed compression energy was relaxed, since less energy was necessary to keep the deformation at a constant level.